Modelling UV/Vis spectroscopy using density functional theory - Wickham, Katherine (2020)
UV/Vis spectroscopy is a key analytical tool to establish information about how molecules interact with light. Naturally this can provide interesting insight into how molecules can be used as dyes and catalysts for example. This work examines the results of UV/Vis spectroscopy with Density Functional Theory (DFT) to understand processes at a finer level. A key focus is the vibrational structure of UV/Vis spectra and how these can be recreated using DFT.